EQ-5D-Y-3L and EQ-5D-Y-5L proxy report: psychometric performance and agreement with self-report - Titi Sahidah Fitriana; Fredrick Dermawan Purba; Elly Stolk; Jan J. V. Busschbach (Health and Quality of Life Outcomes, 2022)
Abstract Background Self-report is the standard for measuring people’s health-related quality of life (HRQoL), including children. However, in certain circumstances children cannot report their own health. For this reason, children’s HRQoL measures often provide both a self-report and a proxy-report form. It is not clear whether the measurement properties will be the same for these two forms. We investigated whether it would be beneficial to extend the classification system of the EQ-5D-Y proxy questionnaire from 3 to 5 response levels. The agreement between self-report and proxy-report was assessed for both EQ-5D-Y measures. Methods The study included 286 pediatric patients and their caregivers as proxies. At three consecutive measurements—baseline, test–retest and follow-up—the proxies assessed the child’s HRQoL using the EQ-5D-Y-3L, EQ-5D-Y-5L, the PedsQL Generic, and matched disease-specific instruments. The proxy versions of EQ-5D-Y-3L and EQ-5D-Y-5L were compared in terms of feasibility, distribution properties, convergent validity, test–retest and responsiveness. Agreement between both EQ-5D-Y proxy versions to their respective self-report versions was assessed at baseline and follow-up. Results The proportion of missing responses was 1% for the EQ-5D-Y-3L and 1.4% for the EQ-5D-Y-5L. The frequency of health state with no problems in all dimensions (11111) was slightly lower for the EQ-5D-Y-5L (21.3% vs 16.7%). Regarding the convergent validity with the PedsQL and disease-specific measures, the proxy versions of EQ-5D-Y-3L and EQ-5D-Y-5L had similar magnitudes of associations between similar dimensions. The means of test–retest coefficients between the two versions of the EQ-5D-Y proxy were comparable (0.83 vs. 0.84). Regarding reported improved conditions, responsiveness of the EQ-5D-Y-5L proxy (26.6–54.1%) was higher than that of the EQ-5D-Y-3L proxy (20.7–46.4%). Except for acutely ill patients, agreement between the EQ-5D-Y-5L proxy and self-reports was at least moderate. Conclusions Extending the number of levels of the proxy version of EQ-5D-Y can improve the classification accuracy and the ability to detect health changes over time. The level structure of EQ-5D-Y-5L was associated with a closer agreement between proxy and self-report. The study findings support extending the EQ-5D-Y descriptive system from 3 to 5 levels when administered by a proxy, which is often the case in the pediatric population.